Evaluation of Soybean Genotypes (Glycine max and G. soja) for Resistance to the Root-Knot Nematode, Meloidogyne enterolobii - Schwarz, Tanner (Plant disease, 2024)
Potential resistance to the root-knot nematode (RKN) Meloidogyne enterolobii in 72 Glycine soja and 44 G. max soybean genotypes was evaluated in greenhouse experiments. Approximately 2,500 eggs of M. enterolobii were inoculated on each soybean genotype grown in a steam sterilized 1:1 sand to soil mixture. Sixty days postinoculation, plants were destructively harvested to determine the host status. The host status of each soybean genotype was determined by assessing root galling severity and calculating the final eggs per root system divided by the initial inoculum, or the reproduction factor (Rf). Five G. soja soybean genotypes were identified as resistant (Rf < 1) to M. enterolobii: '407202', '407239', '424083', '507618', and '639621'. None of the tested G. max soybean genotypes were identified as resistant to M. enterolobii. Some of the G. max genotypes determined to be susceptible to M. enterolobii include 'Hagood', 'Avery', 'Rhodes', 'Santee', and 'Bryan'. The genotype 'Bryan' had the lowest Rf values among the group at 5.06 and 6.67 in two independent trials, respectively, which represents a five- to sixfold increase in reproduction of M. enterolobii. Plant genotypes resistant to RKNs are effective in managing the disease and preserving yield, cost-efficient, and environmentally sustainable, and host resistance is often regarded as the most robust management tactic for controlling plant-parasitic nematodes. Resistance to RKNs in soybean genotypes has been identified for other Meloidogyne species, yet there is currently limited data regarding soybean host status to the highly aggressive nematode M. enterolobii. This study adds to the knowledge of potential native resistance to M. enterolobii in wild and cultivated soybean